The Role of Connecting Rod Length in Enhancing Voltage Output of Translational Electromagnetic Energy Harvesters - Mulyana, Fajar; Risfi Silitonga, M. Prasha; Mafendro, Yuli (Journal of Global Engineering Research and Science, 2024)
This study evaluates the effect of connecting rod stroke length on the performance of a translational electromagnetic energy harvester designed to convert linear mechanical motion into electrical energy. The experimental verification system incorporates a 2850 rpm AC motor linked to an eccentric plate, producing reciprocating motion of a piston embedded with neodymium magnets. These magnets travel through a fixed copper coil, inducing voltage via variations in magnetic flux density. Experiments were conducted using three stroke lengths such as 15 mm, 30 mm, and 45 mm, to across time intervals of 120, 240, and 360 seconds. Key electrical parameters, including direct current (DC) voltage, current, and output power, were measured using a digital AVO meter. Data analysis was performed using Microsoft Excel. The results indicate that the 45 mm stroke length yielded the highest electrical output, with a maximum stored voltage of 4.24 V, current exceeding 0.04 A, and power reaching 0.16 W. Voltage accumulation in highest value occurred at the first 120 seconds and declined at longer durations. It’s due to magnetic losses, resistive heating, and core saturation. These outcomes highlight role of stroke length in improving induction efficiency with increase magnetic flux movement. Moreover, the diminishing performance over time suggests that thermal management and electrical load optimization are necessary to sustain output. The contribution of this study is to offer optional design strategy to generate power in low-frequency vibrational environments such as IoT system and autonomous sensing applications.